Assassin's mark - Larsen, Ward (Larsen, Ward. David Slaton novel, 2023)
"With the help of CIA operative David Slaton, America has shaken off a series of high-tech attacks. Then, just as the threat seems to have receded, the most brazen strike of all: Marine One is brought down in the heart of the capital. The president survives the crash, but is clinging to life by a thread. Once again, Slaton gets the call. With limitless backing from the CIA, the agency's most lethal assassin is dispatched halfway around the world. But as his mission nears completion, he finds himself targeted by a talented adversary, a ruthless young assassin who moves like a ghost, and whose motives are unclear. What is clear is that Trident is not yet finished, and that there is a high-level traitor in the U.S. government. And the only way forward is to topple a conspiracy in the uppermost echelons of Washington"--